Relação entre polimorfismo de caseínas, composição, propriedades do leite de animais Holandês x Zebu e indicadores tecnológicos de queijo - Denise Ribeiro de Freitas (2015)
The aim of this thesis was to investigate the factors that affect the milk protein composition and the casein micelles size in samples of bulk milk and milk from individual cows. This thesis was divided in three chapters. The aim of the first chapter was to analyze the effect of different crossbreeding of 200 cows Holstein x Zebu on casein micelle size. Traits were analyzed by using a linear model including the fixed effects of crossbreeding, somatic cells count and solids non fat. Crossbreeding was associated with casein micelles size. Animals 1/2 and 9/16 exhibited smaller casein micelle size. This result suggests that animals with lower proportion of Holstein race would produce milk with favorable cheese making properties. The aim of the second chapter was to explore the association between milk protein content and casein micelles size, and the effect of casein micelles size upon gel strength and cheese dry mass yield, using a laboratory reduced scale cheese production. A total of 140 bulk tank raw milk samples were collected at dairy farms. Traits were analyzed by using two linear models including only fixed effects. Smaller micelles were associated with the higher amounts of k-casein (k-CN) and blactoglobulin (b-LG), and the lower s-casein (s-CN) content. Factors potentially linked to micellar dissociation, such as high urea content and lower pH were associated with micelles size. The casein micellar size, (without s-CN and k-CN effect), did not affect cheese gel strength, but smaller micelles of casein together with higher fat, lactose, casein and k-CN content exhibited favorable effect on dry matter cheese yield. Overall, the present study provided new insights into importance casein micelle size in to optimize the cheese making process. The aim of the third chapter was to investigate the effects exerted by genetic groups, somatic cell count and CSN1S1 (s1-CN), CSN3 (-CN), LGB (-LG) polymorphisms on milk composition and production of constituents, particularly of protein fractions of milk samples production for animals from different crossbreeding between Holstein and Zebu. Content of the major protein fractions was measured by reversed phase HPLC in individual milk samples of 82 cows. Traits were analyzed by using a linear model including only fixed effects. The genetic groups was divided in G1 (animals 1/2 and 9/16 Holstein x Zebu) and G2 (animals 3/4 Holstein x Zebu) and each genetic group was categorized in high or low CCS. The linear model included days in milk, genes polymorphisms and genetic groups associated with CCS. Effects of genetic groups and CCS affected milk composition, particularly the protein composition. Milk produced by cows from G1 group with lower CCS exhibited higher s1-CN, s2-CN, -CN, -LA e -LG, casein total content. LGB BB polymorphism was associated with increased fat, protein, casein, lactose, total solids, s2-CN e -LA production, and decreased -LG content. CNS3 BB and AB exhibited increased -CN content, and CSN1S1 CC and BC exhibited positively effect on s1- CN concentration.